2012
DOI: 10.1002/anie.201201445
|View full text |Cite
|
Sign up to set email alerts
|

A Sweet Origin for the Key Congocidine Precursor 4‐Acetamidopyrrole‐2‐carboxylate

Abstract: Feeding (Streptomyces) frenzy: Natural products belonging to the pyrrolamide family are defined by their pyrrole‐2‐carboxamide moiety. 4‐acetamidopyrrole‐2‐carboxylate is identified as the key pyrrolamide congocidine precursor (see scheme) through feeding studies using Streptomyces ambofaciens. The biosynthetic pathway of congocidine starts with the carbohydrate N‐acetylglucosamine and involves carbohydrate‐processing enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…In the biosynthesis of 1 , it was proposed that Cgc18 acts iteratively to load the PCP domain of itself and Cgc19 with the same pyrrole precursor, 4-acetylaminopyrrole-2-carboxylate, which is then deacetylated by Cgc14 prior to be assembled into the final skeleton [24], [25]. This model is also hypothesized to be suited to the biosynthesis of tripyrrole skeleton in 2 if the C domain of Cgc18 further catalyzes the condensation between the bipyrrole (the product of the first round of condensation) tethered with Cgc19 and the third pyrrol residue tethered with the PCP domain of Cgc18 [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the biosynthesis of 1 , it was proposed that Cgc18 acts iteratively to load the PCP domain of itself and Cgc19 with the same pyrrole precursor, 4-acetylaminopyrrole-2-carboxylate, which is then deacetylated by Cgc14 prior to be assembled into the final skeleton [24], [25]. This model is also hypothesized to be suited to the biosynthesis of tripyrrole skeleton in 2 if the C domain of Cgc18 further catalyzes the condensation between the bipyrrole (the product of the first round of condensation) tethered with Cgc19 and the third pyrrol residue tethered with the PCP domain of Cgc18 [24].…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that congocidine is assembled by an iterative nonribosomal peptide synthetase (NRPS). In another work, nearly every gene in the congocidine gene cluster is separately inactivated, and LC-MS analysis of the related mutants showed that 4-acetamidopyrrole-2-carboxylate is the key precursor for pyrrolamide biosynthesis [25]. However, the main mechanism underlying the control of pyrrole polymerization, which may be the most intriguing question in oligo-pyrroles NP biosynthesis, has not yet been understood.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic pathways associated with congocidin [117] , chloramphenicol [118] , caprazamycin [119] , clorobiocin and coumermycin A1 production [120] , [121] have all been elucidated. Precursor metabolites for the production of congocidin (3-phospho-glycerate, N-acetyl-glucosamine, sedoheptulose-7-phosphate and cytosine), chloramphenicol (shikimic acid, dichloro-acetyl-CoA), and caprazamycin (uridine, glycine, S-adenosyl-methionine, 3-methyl glutaryl-CoA, fatty acyl-CoA, per-methylated rhamnose) are all derived from glucose-1-phosphate, molecules from the pentose phosphate pathway, 3-phospho-glycerate and acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…27 It should however be noted that a unique pyrrole biosynthesis from fructose-6phosphate (27) was identied by Lautru and co-workers in 2012, operative in Streptomyces ambofaciens (Scheme 3). 28 Brimble's natural product synthesis and medicinal chemistry group in the School of Chemical Sciences. Aer obtaining his undergraduate and doctoral degrees at The University of Auckland, he carried out postdoctoral fellowships in the total synthesis of azaspiracid at Oregon State University (USA), and medicinal chemistry of novel opioid receptor ligands at the University of Bath (UK).…”
Section: Non-enzymatic Originmentioning
confidence: 99%